How Slogans Curate Public Opinion: Hard Lessons from Lakoff and the Linguists. (4th July 2019) - Irvin, Renee A.
Abstract : Many a policy scholar has viewed election results with bewilderment: How can so many people persistently vote against their self-interest? In an attempt to at least partially address this conundrum, this article introduces persuasion techniques that can render good research and evidence largely irrelevant in the court of public opinion. By using U.S. debates about taxation and economic inequality as the linguistic setting of interest, the study illustrates the mechanics of curating public opinion at both ends of the political spectrum. Solutions to economic inequality are complex, yet public opinion can turn toward or away from a proposed policy reform when a few reductive key words distill complexity down to a convincing message: the micro-narrative. Critically examining the broad narrative arc of the policy process is not enough; one must also examine the social construction occurring when word choice is used as persuasive weaponry in the selling of policy reform. The study finishes with a research agenda and a provocation for researchers regarding their role in policy reform. Should academicians remain behind the research curtain, or should they actively critique or even guide the narrative selling of their research?